PENGARUH PROFESIONALISME AUDITOR DAN KUALITAS AUDIT TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS STUDI KASUS PADA BADAN PEMERIKSA KEUANGAN PERWAKILAN PROVINSI JAWA TENGAH - Rachmad Catur Hariady; Haryanto Haryanto (Diponegoro Journal of Accounting, 2017)
This study aimed to examine the effect of the professionalism of auditors and audit quality on the level of materiality considerations in the Audit Board of Indonesia Representatives of Central Java province. The independent variables used in this study, the professionalism of auditors and audit quality, resize obtained by questionnaire.This study uses primary data is a questionnaire that has 53 questions that represent the three variables. The sample in this study is the auditor who works in BPK RI Representative of Central Java province. Data analysis techniques in this study using descriptive statistics and ordinal logistic regression to determine the influence of professionalism of auditors and audit quality on the level of materiality.The results showed that the professionalism of auditors and audit quality findings significant positive effect on the determination of the level of materilitas an inspection by the auditor of BPK RI Representative of Central Java province.